Mother's knowledge factors regarding the incident of stunting in toddlers - Rahma H. Manay; Jasuliana Jasuliana (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Stunting is a chronic nutritional problem in toddlers that has long-term impacts on physical growth, cognitive development, and the quality of human resources. One of the factors that plays a crucial role in preventing stunting is maternal knowledge, as mothers play a key role in ensuring nutritional needs, parenting patterns, and monitoring children's growth and development. Purpose: To determine the relationship between the level of maternal knowledge and the incidence of stunting in toddlers in the working area of ​​the Bonebobakal Health Center, Banggai Regency, Central Sulawesi Province. Method: This study used a quantitative design with a cross-sectional approach. The study was conducted from August to October 2025, with a population of 412 mothers with toddlers. A sample of 80 mothers was selected using a purposive sampling technique. Data were collected using a questionnaire to measure maternal knowledge about stunting and anthropometric measurements to determine toddler stunting status based on WHO standards. Data analysis was performed using SPSS through univariate and bivariate analysis. Results: The results showed that most mothers had good knowledge about stunting. The incidence of stunting was higher among toddlers whose mothers had less knowledge than among mothers with good knowledge. Statistical tests showed a significant relationship between maternal knowledge and stunting in toddlers (p = 0.000). Conclusion: Maternal knowledge is significantly related to the incidence of stunting in toddlers and plays an important role in stunting prevention efforts.